Determination of macronutrients, micronutrients, non-essential elements in milk based-infant formulas by atomic absorption and inductively coupled plasma-optical emission spectroscopy after microwave and ultrasound assisted digestion. Issue 2 (7th February 2017) - Ahmed, Mahmood; Khaleeq, Anum; Munir, Rubina; Huma, Rahila; Muddassar, Muhammad; Naseem, Saadia
ABSTRACT: Microwave and ultrasound procedures for samples preparations were adopted and the elements were determined by validated flame atomic absorption and inductively coupled plasma–optical emission spectrometry. Student's t -test was established whether there was a difference between the sample preparation methods. Trueness of certified values by all methods was ensured which were not differing significantly at 95% level of confidence interval. The highest intensity ratio of magnesium (II)/magnesium (I) was obtained at 1120 radiofrequency value to achieve accurate and reproducible results by inductively coupled plasma–optical emission spectrometry. The value of corresponding correlation coefficient ( r 2 ) were obtained as >0.990 indicating the excellent linearity for concentration range chosen for each element to be determined in commercial samples. Results showed that concentrations of calcium, magnesium, potassium, sodium, chromium, copper, iron, manganese, selenium, and zinc found in commercially available products are in good agreement with label as declared by the manufacturers. Exposure to aluminum, cadmium, and lead from consumption of products under evaluation was estimated and it was in compliance with permissible level suggested by European Commission regulations. Regarding the food safety monitoring, the proposed methods are rapid and met green chemistry approach so that can be implemented in laboratories easily for routine analysis.